STATEMENT OF BERNADETTE DAVISON BANTLY BEFORE THE SAN DIEGO CITY COUNCIL - A BAN ON SMOKING IN ALL PLACES OF EMPLOYMENT WILL NOT SERVE THE PUBLIC GOOD - BANTLY, BERNADETTE (Tufts Archival Research Center, 2007)
Statement made by attorney Bernadette Davison Bantly before the San Diego City Council regarding the expected detrimental effects of a smoking ban in all places of employment. Specifies three key facts in her argument, including the fact that most employers already address workplace smoking, no California court has recognized environmental tobacco smoke (ETS) as causing harm to non-smoking employees, and labor unions oppose legislation restricting workplace smoking. Requests that City Council members vote against the proposed ban on smoking.